Interannual coral Δ14C records of surface water exchange across the Luzon Strait - Ramos, R. D. (2019)
The Luzon Strait (LS) hosts the largest transport of water between the Western Pacific Ocean(WPO) and the South China Sea (SCS). The transport through the strait, dominated by the westwardpropagation of the Kuroshio Intrusion, influences the climate and circulation of the SCS. While numericalmodels have investigated the interannual variability of the transport and subsequent water exchange acrossthe LS, a lack of long‐term on‐site records prevents a general consensus on the transport rates, variability,and drivers. Corals offer high‐resolution, continuous histories of radiocarbon (Δ14C) content of the seawaterdissolved inorganic carbon, allowing us to track changes in ocean transport and circulation through time.Seasonal and annualΔ14C samples from Houbihu, Taiwan, and Palaui, Philippines, located on either side ofthe strait, are compared to the Western Pacific Ocean and SCSΔ14C records to examine the spatial andtemporalΔ14C variability in the region. We calculated the mean transport across the strait using afive‐boxmixing model and identified its potential drivers. The mean amount of water exchanged across the straitfrom 1970 to 1999 was 2.2 Sv, ranging from−13.4 to 16 Sv, where a positive (negative) value indicates netflow into (out of) the SCS. A weaker East Asian Winter Monsoon increases the contribution of the SCSoutflow on the Kuroshio Intrusion‐dominated LS, while the El Niño–Southern Oscillation primarily drivesthe intrusion into the SCS. These results provide support to the dominant control of El Niño–SouthernOscillation on the long‐term ocean circulation variability in this region.